Aptamer functionalized silver clusters for STED microscopy. Issue 20 (16th February 2017) - Wang, Lan; Ta, Haisen; Ullal, Chaitanya; Wang, Fu; Wang, Chuanyi; Dong, Guohui
Abstract : Novel STED probe was prepared through aptamer functionalized silver clusters, which preserve specific affinity with smaller size and more photostability. Abstract : Alternative to traditional dye or fluorescent protein, a novel stable probe for stimulated emission depletion (STED) microscopy is critically needed. In this work, aptamer functionalized Ag clusters with high photostability were successfully prepared. Moreover, improved resolution has been observed both at the single particle level and in specific cell structures, suggesting that aptamer functionalized Ag clusters are promising candidates for STED microscopy.